The Soviet Industrialization and GULAG - Meerovich, Mark (project baikal, 2017)
The article is based on the book by V. A. Berdinskikh and V. I. Menkovsky (Berdinskikh & Menkovsky, 2017). The repressive policy of the Soviet government toward the Soviet people is viewed in the context of the aim to form the most powerful military and industrial complex set by the party leaders under the name of “Industrialization Program”. As a state entity of the territorial and economic activity, GULAG was committed to certain production tasks, which caused the necessity to provision it with a slave “labour fund”. The prehistory of the formation of the slave labour structures in the USSR in the form of labour armies is also viewed in the article.